Length rather than year‐round spawning, affects reproductive performance of RAS‐reared F‐generation pikeperch, Sander lucioperca (Linnaeus, 1758) – Insights from practice. (3rd February 2018) - Schaefer, F. J.; Overton, J. L.; Kloas, W.; Wuertz, S.
Summary: The continuous production of large numbers of high quality gametes is essential for aquaculture, particularly in candidate species, such as pikeperch, Sander lucioperca (L.). The common practice of year‐round reproduction is under suspicion of inflicting adverse effects on the quality of the gametes through the disturbance of endogenous rhythms. We hypothesized that such perturbation does not affect RAS‐reared F‐generation broodstock. Reproductive performance (number of eggs) and gamete quality (fertilization and hatching rate) were assessed over the course of 3 years covering six independent, photothermal shifted spawning seasons in a commercial pikeperch hatchery ( n = 31 egg batches of F‐generation fish in total). No substantial differences in fertilization or hatching rates could be detected between the individual spawning seasons. Fecundity varied, but there are indications for a size effect on female fecundity with intermediate sized females producing higher number of eggs ( 65–70 cm). Low egg quality could be detected in batches of very large fish. In conclusion, size‐specific broodstock composition, but not year‐round reproduction of F‐generation pikeperch spawners affects the reproductive performance.